Anti-quorum Sensing and Anti-biofilm Activity of Delftia tsuruhatensis Extract by Attenuating the Quorum Sensing-Controlled Virulence Factor Production in Pseudomonas aeruginosa - Singh, Vijay K.; Mishra, Avinash; Jha, Bhavanath (Frontiers in Cellular and Infection Microbiology, 2017)
Multidrug-resistance bacteria commonly use cell-to-cell communication that leads to biofilm formation as one of the mechanisms for developing resistance. Quorum sensing inhibition is an effective approach for the prevention of biofilm formation. A Gram-negative bacterium, Delftia tsuruhatensis SJ01, was isolated from the rhizosphere of a species of sedge (Cyperus laevigatus) grown along the coastal-saline area. The isolate SJ01 culture and bacterial crude extract showed quorum sensing inhibition activity in the biosensor plate containing the reference strain Chromobacterium violaceum CV026. A decrease in the violacein production of approximately 98% was detected with the reference strain C. violaceum CV026. The bacterial extract (strain SJ01) exhibited anti-quorum sensing activity and inhibited the biofilm formation of clinical isolates wild-type Pseudomonas aeruginosa PAO1 and P. aeruginosa PAH. A non-toxic effect of the bacterial extract (SJ01) was detected on the cell growth of the reference strains as P. aeruginosa viable cells were present within the biofilm. It is hypothesized that the extract (SJ01) may change the topography of the biofilm and thus prevent bacterial adherence on the biofilm surface. The extract also inhibits the motility, virulence factors (pyocyanin and rhamnolipid) and activity (elastase and protease) in P. aeruginosa treated with SJ01 extract. The potential active compound present was identified as 1,2-benzenedicarboxylic acid, diisooctyl ester. Microarray and transcript expression analysis unveiled differential expression of quorum sensing regulatory genes. The key regulatory genes, LasI, LasR, RhlI, and RhlR were down-regulated in the P. aeruginosa analyzed by quantitative RT-PCR. A hypothetical model was generated of the transcriptional regulatory mechanism inferred in P. aeruginosa for quorum sensing, which will provide useful insight to develop preventive strategies against the biofilm formation. The potential active compound identified, 1,2-benzenedicarboxylic acid, diisooctyl ester, has the potential to be used as an anti-pathogenic drug for the treatment of biofilm-forming pathogenic bacteria. For that, a detailed study is needed to investigate the possible applications.